Impact of DNA repair and reactive oxygen species levels on radioresistance in pancreatic cancer. (June 2021) - Nguyen, Lily; Dobiasch, Sophie; Schneider, Günter; Schmid, Roland M.; Azimzadeh, Omid; Kanev, Kristiyan; Buschmann, Dominik; Pfaffl, Michael W.; Bartzsch, Stefan; Schmid, Thomas E.; Schilling, Daniela; Combs, Stephanie E.
Highlights: Fractionated radiation can generate isogenic RR cancer cell lines. Acquired radioresistance was validated in vitro and in vivo. RR cell lines demonstrate enhanced DNA repair capacity and reduced ROS levels. Migration and invasion are influenced differently by the acquired radioresistance. Abstract: Purpose: Radioresistance in pancreatic cancer patients remains a critical obstacle to overcome. Understanding the molecular mechanisms underlying radioresistance may achieve better response to radiotherapy and thereby improving the poor treatment outcome. The aim of the present study was to elucidate the mechanisms leading to radioresistance by detailed characterization of isogenic radioresistant and radiosensitive cell lines. Methods: The human pancreatic cancer cell lines, Panc-1 and MIA PaCa-2 were repeatedly exposed to radiation to generate radioresistant (RR) isogenic cell lines. The surviving cells were expanded, and their radiosensitivity was measured using colony formation assay. Tumor growth delay after irradiation was determined in a mouse pancreatic cancer xenograft model. Gene and protein expression were analyzed using RNA sequencing and Western blot, respectively. Cell cycle distribution and apoptosis (Caspase 3/7) were measured by FACS analysis. Reactive oxygen species generation and DNA damage were analyzed by detection of CM-H2 DCFDA and γH2AX staining, respectively. Transwell chamber assays were used to investigate cell migration and invasion. Results: The acquired radioresistance of RR cell lines was demonstrated in vitro and validated in vivo . Ingenuity pathway analysis of RNA sequencing data predicted activation of cell viability in both RR cell lines. RR cancer cell lines demonstrated greater DNA repair efficiency and lower basal and radiation-induced reactive oxygen species levels. Migration and invasion were differentially affected in RR cell lines. Conclusions: Our data indicate that repeated exposure to irradiation increases the expression of genes involved in cell viability and thereby leads to radioresistance. Mechanistically, increased DNA repair capacity and reduced oxidative stress might contribute to the radioresistant phenotype.